ASSESSMENT OF ANTINEOPLASTIC POTENTIAL OF ANNONA RETICULATA LINN. ON HUMAN CANCER CELL LINES - p, RajaRajan; R, Senthil Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The present study was undertaken to establish the antineoplastic potential of Annona reticulata on human cancer cell lines, viz., squamous cell carcinoma 9 (SCC9), MCF-7 (human breast adenocarcinoma), A549 (lung adenocarcinoma), and HCT116 (colorectal carcinoma) cells. Methods: The study was performed through MTT, cell cycle (G2M), and DNA fragmentation assays. Cells inhibited in MTT assay were subjected to cell cycle analysis and DNA fragmentation, respectively. Results: The extracts showed dose-dependent growth inhibition of SCC9, MCF-7, A549, and HCT116 cells. In contrast to HCT116 and A549 cells, which exhibited cytotoxicity at a higher concentration with IC50 value of 271.7 and 296 µg/ml, the extract treated SCC9 and MCF-7 cells exhibited significant cytotoxicity at a lower concentration with IC50 value of 49.47 and 52.65 µg/ml, respectively. The treated A549 and MCF-7 cells showed cell cycle arrest up to 7.07% and 14.42%, respectively, at G2/M phase of cell cycle. DNA fragmentation was not observed in both A549 and MCF-7 cells treated with A. reticulata extract at a concentration of 320 µg/ml. Conclusion: Encouraging preliminary results emphasize the necessity for further research on characterization of individual compounds from this extract and advocate it as a good source of anticancer agent for certain types of cancer. Keywords: Annona reticulata, Anticancer activity, MTT, G2M and DNA fragmentation.